Terminology Characterizing a Wide Range of Objects - Shaymanovich, Xasan Abdinazarov (Researchparks Publishing, 2023)
A language consists of a variety of branches of science, that include transportation, technology, and instrumentation and devices. In particular, in English system of petroleum engineering there are a lot of terminology denoting different means of objects, for instance, terms relating to transportation of oil and gas, terminology regarding technology, and tools, devices which engineers deploy in their workplaces. However, those terms were invented and nominated in the English and Uzbek languages differently. This paper mainly focuses on the issues concerning nominating the terms between two languages. Moreover, the collected data indicated that there are an increasing numbers of terminology characterizing terminology in the field of petroleum engineering.